(untitled) (PIONIR: JURNAL PENDIDIKAN, 2021)
Education and the educational process continue to experience changes, both scientific changes, as well as changes that are planned according to abilities and desires. The quality of graduates who are qualified and in accordance with the needs of the community will have a great influence on organizational productivity. A developed country is a country that has a quality society. Society is said to be qualified if the individuals who make up the community are educated or have knowledge. To be able to master science and technology, one must study and undergo education. Based on the explanation of the Republic of Indonesia Law No. 20 of 2003 concerning the national education system, setting the vision of national education is the realization of the education system as a strong and authoritative social institution to empower all Indonesian citizens to develop into quality Indonesian people so that they are able and proactively respond to the challenges of the times. always changing. One of its missions is to improve the readiness of inputs and the quality of the educational process to optimize the formation of a moral personality.